The impact of R&D tax incentives on corporate innovation in developing ASEAN countries - Hayati, Sri Rezki; Nuryakin, Chaikal (Jurnal Ekonomi & Studi Pembangunan, 2026)
Innovation is widely recognized as a key source of growth and competitiveness, particularly in developing countries, making policies such as R&D tax incentives increasingly important. This study analyzes the impact of implementing R&D tax incentives on firms' propensity to innovate in five selected developing ASEAN countries (Indonesia, Malaysia, Vietnam, Cambodia and the Philippines), and how variations in designs and mechanisms affect this relationship. The study uses firm-level data from the two most recent rounds of the World Bank Enterprise Survey (WBES), and applies a panel logit fixed-effects model to a dataset of 483 firms to facilitate comparative analysis over time. This study therefore fills a significant gap in the literature by offering cross-country, firm-level evidence on how changes to R&D tax incentive design can affect innovation outcomes across firms located within developing ASEAN economies. Findings suggest that firms in countries with R&D tax incentives are 4.38 times more likely to innovate than those in countries without such policies. Nonetheless, the success of such incentives is conditional on macro and microeconomic circumstances as well as the mechanism of the incentives. Specifically, the analysis differentiated input-based incentives linked to firms' R&D expenditures from output-based incentives that are based on achieving specific innovation outputs (patents or new products) by firms. The results suggest that output-based mechanisms lead to less innovation than expenditure based schemes. The overall results reinforce that it is not just the adoption but also the design of R&D tax incentive policies that matters, suggesting that policymakers in developing countries should invest in flexible, input-based approaches rather than rigid approaches tied to specific innovation outputs.